Effects of Moderate Electric Field Pretreatment on the Efficiency and Nutritional Quality of Hot Air-Dried Apple Slices - Deryanur Kalkavan; Nese Sahin Yesilcubuk (Foods, 2025)
This study investigates the effects of electric field pretreatment parameters such as electric field strength (0.1–0.2 kV/cm), waveform (sinusoidal vs. square), and application mode (continuous vs. pulsed) on the quality attributes of dried Fuji apple slices, including ascorbic acid (vitamin C) retention, β-carotene content, and hydroxymethylfurfural (HMF) formation. Electric-field-treated samples were compared to untreated controls after convective drying at 75 °C. Results revealed that vitamin C was significantly influenced by waveform, with sinusoidal waves preserving about 27% more vitamin C than square waves, likely due to reduced oxidative degradation from gentler electroporation. Conversely, square waves caused the highest β-carotene losses (25% vs. control), attributed to prolonged peak voltage destabilizing carotenoids. HMF formation was reduced by 10–23% in electric-field-treated samples compared to controls, linked to accelerated drying rates limiting Maillard reaction time. Low electric field strengths (0.1–0.15 kV/cm) enhanced antioxidant activity; however, higher intensities showed a potential decline. The square waveform had a more detrimental effect on phenolic compounds than the sinusoidal waveform. These findings suggest that low electric field pretreatment, particularly with sinusoidal waveforms at 0.2 kV/cm, enhances drying efficiency while balancing nutrient retention and HMF mitigation, offering a promising strategy for producing high-quality dried fruits.